An Analysis of Characterization of Main Character in the Up 2009 Movie by Pete Docter - Ida Bagus Gde Nova Winarta; I Putu Andri Permana; Gede Teguh Yudistira (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
The tittle of this thesis is An Analysis Of Characterization Of Main Character In The UP 2009 Movie By Pete Dokter. This movie tell about a old man, the name is Carl Fredricksen who full fills his promise going to the paradise fall using a flying house with many ballons and Russel, in his journey Carl and Russel pass a lot obstacles and the finally arrive in Paradise Falls. For the analysis of the main characters obtained in the UP film, there are several characters such as impolite, wild, cruel, bad thoughts, smart care, angry caring, Brave. The data which had been collected were analyzed descriptively based on the theory Kenney (1966) and theory Wellek and Warren (1956). The main character was analyzed into four categories which is simple(flat) character, complex(round) character, dynamic character and static characterFrom the result analisys there are Three dimension, from the three dimensions, there is 1 Physiological Dimension data, 19 Psychological Dimension data, and 2 Sociological Dimension data. So, in conclusion the most prominent dimension of Mr. Fredricksen is Psychological Dimension which contains 19 data.